Geopolitical Consequences of the 21st Century New Maritime Silk Road for Southeast Asian Countries - Péter Klemensits (Contemporary Chinese Political Economy and Strategic Relations: An International Journal, 2018)
One of the major elements of the One Belt, One Road initiative launched by China in 2013 is the concept of the 21st Century Maritime Silk Road. The author aims to give a summary of the 21st Century Maritime Silk Road, and the Chinese intentions in general, then to present in detail the participation of the Southeast Asian countries in the project, and the geopolitical consequences of this cooperation for the region. Of all the ASEAN countries, Indonesia showed the greatest enthusiasm towards the Chinese plans, but Malaysia, Myanmar and the Philippines have aspired to join the Chinese-led project as well. According to my conclusion, the Maritime Silk Road has great significance in a geopolitical sense, because it has become the decisive element of Chinese foreign policy. In the case ofASEAN countries, it especially has a greater strategic goal: reinforcing China’s influence in the region in the field of both economy and politics enjoys priority, due to the rivalry between China and the United States.